6 Trends Framing the State of AI and ML - Magoulas, Roger; Swoyer, Steve (O'Reilly Media, Inc., 2020)
O'Reilly usage analysis shows continued growth in AI/ML and early signs that organizations are experimenting with advanced tools and methods.